The Effect of Active Cycle of Breathing Techniques (ACBT) on Shortness of Breath and Facilitation of Airway Clearance in Obstructive Pulmonary Disease: Literature Review - Mahadewi, Ni Luh Putu Citra; Anantari, Ni Putu Diah; Putra, Ketut Sutirama Cagi; Laksmi, I Gusti Agung Ayu Ari Candra; Prasana, I Gede Eka Juli; Jeviana, Ariezta (Universitas Muhammadiyah Surakarta, 2025)
Introduction: Obstructive lung disease is characterised by airflow obstruction due to airway narrowing or damage. The Active Cycle of Breathing Techniques (ACBT) is designed to address issues arising from this by mobilising and clearing secretions from the airways, as well as improving breathing mechanics to reduce dyspnea. This study aims to determine the effect of Active Cycle of Breathing Techniques (ACBT) on dyspnea and airway clearance in cases of obstructive lung disease. Results: A review of 7 previous studies revealed the effects of Active Cycle of Breathing Techniques (ACBT) in reducing dyspnea and clearing the airways in patients with obstructive lung disease. Method: This study uses a literature review method. Articles published from 2014 to 2024, related to the effects of ACBT on airway clearance in patients with obstructive lung disease, were identified through relevant databases (Google Scholar, PubMed, and ScienceDirect) using predetermined keywords. Articles that met inclusion criteria, such as appropriate study design, publication year, and language, were selected for analysis. Results: A review of 7 previous studies revealed the effects of Active Cycle of Breathing Techniques (ACBT) in reducing dyspnea and clearing the airways in patients with obstructive lung disease. Conclusion: There is an impact of Active Cycle of Breathing Techniques (ACBT) exercises in reducing dyspnea and clearing the airways in patients with obstructive lung disease